P–418 Different immunoregulatory components at the decidua basalis of oocyte donation pregnancies. (6th August 2021) - Va. Bentem, K; Bos, M; Va. de. Keur, C; Kapsenberg, H; Lashley, L; Eikmans, M; Va. de. Hoorn, M L
Abstract: Study question: Is the number of regulatory T-cells (Tregs) and immunoregulatory cytokines in the decidua basalis of oocyte donation (OD) pregnancies different compared to naturally conceived pregnancies? Summary answer: This study suggests that the immunoregulation at the fetal-maternal interface in OD pregnancies with a higher amount of fetal-maternal HLA mismatches appears to be altered. What is known already: Tregs and related immunoregulatory cytokines, such as interleukins, transforming growth factor-β, and galectin–1, play a key role in maintaining tolerance at the decidua basalis in human pregnancy. Previous studies observed decreased numbers of decidual Tregs in miscarriage and preeclamptic pregnancies. These complications occur in higher frequencies in OD pregnancies, which are characterized by more fetal-maternal human leukocyte antigen (HLA) mismatches compared with naturally conceived (NC) and non-donor in vitro fertilization (IVF) pregnancies, since the fetus obtains paternal and donor-derived HLA genes. Consequently, the maternal immune system has to cope with greater immunogenetic dissimilarity. Involved immunoregulatory mechanisms however remain poorly understood. Study design, size, duration: This case-control study included 27 OD, 11 IVF, and 16 NC placentas of uncomplicated pregnancies, which were collected after delivery at 37–42 weeks of gestation between 2005 and 2013. Clinical data, maternal peripheral blood and umbilical cord blood were collected. Participants/materials, setting, methods: Decidua basalis was dissected from the placentas, and processed to formalin-fixed, paraffin-embedded slices (4 µm). Immunohistochemical staining for FOXP3, interleukin 10, interleukin 6, galectin–1, transforming growth factor-β, and Flt–1 was performed. Semi-quantitative (FOXP3+ Tregs) and computerized analysis (cytokines), using Image-J software, were executed. Maternal peripheral blood and fetal umbilical cord blood were typed for HLA class I and II, using the Sequence Specific Oligonucleotides PCR technique, to calculate the number of fetal-maternal HLA mismatches. Main results and the role of chance: All the deciduae basalis of OD, IVF and NC pregnancies showed FOXP3+ Tregs. No significant differences were found when comparing the three groups for the mean number of FOXP3+ Tregs. However, when the amount of fetal-maternal HLA mismatches was related to the percentage of FOXP3+ Tregs, the Tregs were significantly higher in pregnancies with 4–6 HLA class I mismatches (n = 16), than in those with 0–3 HLA class I mismatches (n = 38; p = 0.029). Furthermore, OD pregnancies express less interleukin 10, interleukin 6, galectin–1 and Flt–1 in the decidua basalis compared to NC pregnancies. Moreover, the amount of interleukin 10 was significantly lower with 3–4 fetal-maternal HLA class II mismatches (p = 0.032). Limitations, reasons for caution: This study is limited by a small sample size. Moreover, only term placentas were collected. It would be worthwhile investigating immunological alterations in the decidua throughout the whole gestation, since maternal adaptation of the fetal allograft could be more prominent early in pregnancy. Wider implications of the findings: Unravelling the mechanisms of immunomodulation during OD pregnancy, reflected by a high level of fetal-maternal dissimilarity, could help to reach the ultimate goal in transplantation; the induction of donor-specific tolerance. In addition, it might help to understand the development of complications in OD pregnancy. Trial registration number: Not applicable